The acute effect of a multi-modal plyometric training session on field-specific performance measures - Doma, K.; Burt, D.; Connor, J. D. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Plyometric and resistance exercises are known to cause exercise-induced muscle damage (EIMD). Thus, this study examined the impact of EIMD on various field-specific performance measures following a training session that combined plyometric and resistance exercises. METHODS: Nine competitive Ultimate Frisbee players undertook a training session consisting of several modes of plyometric and resistance exercises. Indirect markers of muscle damage (i.e., creatine kinase [CK] and delayed onset of muscle soreness [DOMS]) and field-specific performance measures (i.e., run-up vertical jump, standing broad jump, linear sprint and repeated agility) were measured prior to, 24 hours (T24) and 48 hours (T48) post training. RESULTS: The combined plyometric and resistance training session significantly increased muscle damage markers at T24 (CK: 326.5±210.4% and DOMS: 343.3±181.6%) and T48 (CK: 969.2±1262.3% and DOMS: 371.1±179.3%). The jump performance measures were significantly reduced at T24 (run-up vertical jump -5.5±6.3% and standing broad jump -4.7±3.7%) and T48 (run-up vertical jump -4.2±5.1% and standing broad jump -5.0±4.4%). Furthermore, completion times for linear sprint performance was significantly increased at T24 (4.5±3.4%) and T48 (7.2±4.2%), whilst the average completion time for the repeated agility protocol was significantly increased at T24 (1.4±1.4%). CONCLUSIONS: Competitive team sport athletes may require at least 48 hours of recovery when implementing field-based conditioning sessions after a training session that combines plyometrics and resistance exercises, particular if unfamiliar with such training modalities.